EVALUASI IMPLEMENTASI PENDIDIKAN MADRASAH MA’ARIF DI KABUPATEN JOMBANG - Alvin Mustikawan (El-QUDWAH, 2007)
This research is aimed at investigating the implementation of education of Ma’arif Islamic school in Jombang regency, especially the characteristics of the students, teachers, the facilities and basic facilities, students’ motivation in learning, teacher’s preparation in teaching, the implementation of instruction by the teacher, students’ participation in the process of teaching and learning, the relationship between students and the teacher, and also students’ achievement. This research is an evaluation research by using Stake approach with quantitative data. Data were obtained through questioner, observation, interview, and documentation. The data were analyzed by using quantitative approach. The analysis technique of this research used descriptive quantitative analysis technique. The findings showed that in the four Islamic schools that were studied, the parents, generally, work in agriculture; and they were graduated from SMA or MA. Students’ motivation in learning can be considered good. Besides, most of the teachers have taken undergraduate degree. The teachers’ preparation before the process of teaching and learning has been managed well. The facilities and basic facilities have not fulfilled the need of students and teachers yet.  Moreover, the implementation of instructional material can go well. However, students’ participation was still considered less. Despite of that, the relationship between students and teacher can be considered good. Students’ achievement in these schools has been meeting the criteria. Moreover, the academic achievement that includes students’ behavior was considered good. Keyword: Evaluation, Implementation of Education, Islamic School